Kalmyk-Cossacks of the Don Regiments in the Borodino Battle of 1812 - Konstantin Maksimov (Oriental Studies, 2018)
The article is devoted to the participation of the Kalmyks of the Don Cossack regiments in the Borodino Battle of 1812. The work is to a considerable extent based on the materials of the Russian State Archive of Military History and State Archive of the Rostov region.